Impact of Implementation Information Technologyon Accounting - Sarjito Surya (Bandar Lampung University (UBL), 2012)
In recent years business is growing fast and faster and this is the reason for investment in information technology (IT)specially on accounting department. The implementation of an IT improves information flow, reduce costs, establishlinkage with suppliers and reduce response time to customer needs. This paper focuses on a sample Indonesian companies in Bandung, West Java, Indonesia investigates the implementation of IT on accounting, the benefits that users have achieved andthe influence of implementation of IT on accounting.The results indicate a better level on accuracy, better reporting, using accounting software, functionality increasing and last dimension is faster reporting provided by implementation of IT on accounting.